Engineering Geological Characteristics of the Residual Soil, Lower Quaternary Sediments in Kertajati Region, Majalengka, West Java - Untung Sudarsono; G. Hasibuan (Indonesian Journal on Geoscience, 2011)
DOI: 10.17014/ijog.v6i3.125Only few engineering geological researches on residual soil have been conducted in Indonesia, whereas many infrastructure projects take place on undulating area and mountainous area which are composed of residual soils. The paper discusses residual soil characteristics of the Lower Quaternary sediment (Qos) in Kertajati area, Majalengka. The methodology of the research consists of engineering geological mapping, in situ test using 2.5 ton penetrometer, sampling and laboratory test for index properties, Atterberg limits, grain size analysis, and strength tests. Field test analysis data show that the thickness of residual soil resting on the basement rock in the study area varies from 2.40 - 14.20 m. Upwards, it comprises sands, silts, and clays, respectively. Laboratory analysis data indicate that the residual soil is dominated by fine-grained fraction, composed of high plastic clay (CH). Relationship among engineering geological parameters was analysed using linear regression and tested using statistic method t-test to find real correlation among variables within 95 - 90% significance level.. Based on the test, there are real positive correlation with 19 degree of freedom and 5% and 10% level of significance are found in between plasticity indexes (IP) and liquid limits (LL), between plasticity indexes (IP) and clay contents (C), between specific gravities (G ) and clay contents (C). The real negative correlation with nine degree of freedom and 5% and 10% level of significance occurs in between cohesion (c) dengan friction angle (φ). Corelation between degree of saturation (G ) and clay contents (C) with 19 degree of freedom is found in 10% level of significance.